2004
DOI: 10.1152/jn.00097.2004
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Activates a Sucrose-Responsive Gustatory Neural Pathway

Abstract: Lemon, Christian H., Susan M. Brasser, David V. Smith. Alcohol activates a sucrose-responsive gustatory neural pathway. J Neurophysiol 92: 536 -544, 2004. First published February 25, 2004 10.1152/jn.00097.2004. A strong positive association exists between the ingestion of alcohol and sweet-tasting solutions. The neural mechanisms underlying this relationship are unknown, although recent data suggest that gustatory substrates are involved. Here, we examined the role of sweet taste receptors and central neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 69 publications
3
73
0
Order By: Relevance
“…It should be noted that some strains may respond to adulteration of ethanol solutions with other compounds by increasing intake, as D2 mice have been shown to increase their intake of and two-bottle preference for ethanol when it was added to non-alcoholic beer (Grisel et al, 2007). Finally, a recent study has shown that in rats, sucrose-responsive neurons in the nucleus of the solitary tract showed a much larger, concentration-dependent response to an oral ethanol stimulus than sucroseunresponsive cells (Lemon et al, 2004). This suggests a possible physiological basis for differential modulation of ethanol's tase-related cue properties in saccharin preferring versus non-preferring genotypes.…”
Section: Discussionmentioning
confidence: 94%
“…It should be noted that some strains may respond to adulteration of ethanol solutions with other compounds by increasing intake, as D2 mice have been shown to increase their intake of and two-bottle preference for ethanol when it was added to non-alcoholic beer (Grisel et al, 2007). Finally, a recent study has shown that in rats, sucrose-responsive neurons in the nucleus of the solitary tract showed a much larger, concentration-dependent response to an oral ethanol stimulus than sucroseunresponsive cells (Lemon et al, 2004). This suggests a possible physiological basis for differential modulation of ethanol's tase-related cue properties in saccharin preferring versus non-preferring genotypes.…”
Section: Discussionmentioning
confidence: 94%
“…Rodents also perceive similarities in the oral properties of ethanol and sweet-tasting stimuli, as conditioned aversions to the orosensory features of ethanol generalize to sucrose mixtures in rats (Di Lorenzo et al 1986;Kiefer et al 1990; Kiefer and Lawrence 1988;Kiefer and Mahadevan 1993) and taste aversions to sucrose alone generalize to ethanol in C57BL/6J (B6) mice (Blizard and McClearn 2000). Furthermore, neurophysiological studies across multiple species have demonstrated positive associations between responses to oral alcohol and sweet stimuli in peripheral gustatory fibers (Danilova and Hellekant 2000;Diamant et al 1963;Hellekant et al 1997;Sako and Yamamoto 1999) and central taste-sensitive neurons (Brasser et al 2010;Di Lorenzo et al 1986;Lemon et al 2004;Lemon and Smith 2005). Selective antagonism of sweet taste receptors also directly suppresses oral responses to alcohol by gustatory-sensitive sensory neurons (Lemon et al 2004;Sako and Yamamoto 1999), implicating sweet receptors in the transduction of alcohol taste.…”
mentioning
confidence: 99%
“…In phase 1, we analyze taste responses from a large number of NST neurons, some drawn from our files (Lemon et al, , 2004Lemon and Di Lorenzo, 2002) and others newly recorded. All neurons were sampled from naive adult male Sprague Dawley rats under urethane anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…All neurons were sampled from naive adult male Sprague Dawley rats under urethane anesthesia. For newly acquired cells, details of the surgical and recording procedures have been reported previously (Lemon et al, , 2004Lemon and Smith, 2005). Briefly, conventional single-unit electrophysiological methods were used to record trains of action potentials from gustatory neurons in the NST.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation